PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN GEOGEBRA TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI TEOREMA PYTHAGORAS SISWA KELAS VIII SMPN 23 MATARAM TA 2025/2026 - Pratama, Izza; Azmi, Syahrul; Primajati, Gilang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using GeoGebra as a learning medium on students’ mathematics learning outcomes in the Pythagorean theorem material among eighth-grade students of SMP Negeri 23 Mataram in the 2025/2026 academic year. This research employed a quasi-experimental method with a posttest-only control group design. The population in this study consisted of all eighth-grade students of SMP Negeri 23 Mataram in the 2025/2026 academic year. The sample was determined using a saturated sampling technique, in which the entire population consisting of two classes was taken directly as the sample. Class VIII B was assigned as the experimental group and class VIII A as the control group. The experimental group used GeoGebra as the learning medium, while the control group used PowerPoint. The research instruments included observation sheets, learning outcome tests, and learning tools. Data analysis using the t-test showed that the calculated value = 2,194 was greater than = 1,999. This means that there was a difference in the average mathematics learning outcomes between students in the experimental class who used GeoGebra and students in the control class who used PowerPoint. The average post-test score of the experimental class was 74,19, which was higher than the control class score of 63,13, with the effect categorized as moderate based on the effect size value of = 0.558. Thus, it can be concluded that there is an effect of using GeoGebra as a learning medium on the mathematics learning outcomes of eighth-grade students of SMP Negeri 23 Mataram in the Pythagorean theorem material for the 2025/2026 academic year.